Sunny Side Up?: Solarpunk Futures for a Dying World. Issue 1 (1st April 2023) - Martens, Reuben
Abstract : This article aims to challenge the "solar" in solarpunk, a genre of speculative fiction that features hopeful, socially just, green energy futures. Rather than an expression of solarity —"an intersectional, equitable, and ethical response to [petrocultural] regimes"—I argue that solarpunk imagines solarculture : a continuation of petrocultural neoliberalism, where oil has been substituted for renewables. After an exploration of solarpunk's (problematic) imaginings through the Glass and Gardens: Solarpunk Winters (2020) anthology, this article offers a way out of the solarcultural status quo by considering the interdisciplinary fiction of The Weight of Light: A Collection of Solar Futures (2018) as a functional example of how to imagine the complexities of our energy future more fully.